Cross Sectional Attitudes of Public Sculpture Matrix in Southwestern Nigeria - Moses Akintunde Akintonde (Journal of Visual Art and Design, 2016)
Public outdoor sculpture practice in the Southwestern Nigeria entails different types of attitudes. These attitudes are discernable from the stage of commissioning of work, its conceptualization to the display and uses in the public sphere generated diverse fundamental, constant technical issues. Some are explicitly alluring while others are absurd, fleeting and injurious to the practice. However, whatever attitude advanced in the public outdoor sculpture practice, it has not been discussed cross sectionally. The inadequate scholarship attention on the attitudinal issues in outdoor sculpture certainly created art historical gap apt to make the study of contemporary Nigeria art incoherent. Apparently, attitudinal studies certainly involve psychological measurement - a type of instrument that does not required descriptive survey. For this reason, the study was based on qualitative methods. The study categorised various attitudes in outdoor sculpture practice in the studied area into pre-unveiling, unveiling and post unveiling stages and critically examined them. Some attitudes in the practice of the art were observed to be stimulant for advancement; invariably others are clearly incongruous to the spirit of typical Yoruba societal value orientation in orderliness, therefore degrading and detrimental to the development of the outdoor sculpture in the public sphere.Keywords: Art patron; cross sectional attitude; outdoor sculpture; post-unveiling; pre-unveiling; public art; Southwestern Nigeria; unveiling.